Bataan munitions manufacturing complex - Dizon, Jonathan D. (Manila : National University, 2000)
It aims to upgrade the manufacturing lines including the rehabilitation of old equipment and acquisition of new equipment to replace the unserviceable ones and to balance or increase the output of the production system.